Topics of significance for international development from religions and COVID-19 research. Issue 8 (17th November 2022) - Trotta, Susanna; Wilkinson, Olivia; Marshall, Katherine
ABSTRACT: This review article looks at trends from academic articles published on religions and the COVID-19 pandemic between March 2020 and October 2021 in relation to their relevance for international development and global health researchers, policy makers, and practitioners. It focuses on mental health and gender-based violence. The literature shows that the use of religion and spiritual support as a coping mechanism when experiencing mental health issues and/or being exposed to gender-based violence are key topics for religions and COVID-19 research, but that neither topic is always appropriately considered when planning and implementing public health interventions.